Natural modulation of redox status throughout the ontogeny of Amazon frog Physalaemus ephippifer (Anura, Leptodactylidae) - Monteiro, João Pedro Pantoja; Santos, Carla Carolina Miranda dos; Queiroz, João Paulo Moura de; Chagas, Rafael Anaisce das; Loureiro, Sarita Nunes; Nauar, Alana Rodrigues; Souza-Ferreira, Maria Luiza Cunha; Cardoso, Adauto Lima; Martins, Cesar; Petrović, Tamara G.; Prokić, Marko D.; Oliveira-Bahia, Verônica Regina Lobato; et al. (Springer Nature, 2024)
During their development, amphibians undergo various physiological processes that may affect their susceptibility to environmental pollutants. Naturally occurring fluctuations caused by developmental events are often overlooked in ecotoxicological studies. Our aim is to investigate how biomarkers of oxidative stress are modulated at different stages of larval development in the Amazonian amphibian species, Physalaemus ephippifer. The premetamorphosis, prometamorphosis and metamorphic climax stages were used to analyze total antioxidant capacity (ACAP), glutathione S-transferase (GST) activity, lipid peroxidation (LPO) levels and the expression of genes nrf2, gst, gsr (glutathione reductase) and gclc (glycine-cysteine ligase, catalytic subunit). Although there was no difference in ACAP and the genes expression among the studied stages, individuals from the premetamorphosis and prometamorphosis showed higher GST activity than ones under the climax. LPO levels were highest in individuals from the metamorphic climax. The present study suggests that the oxidative status changes during ontogeny of P. ephippifer tadpoles, especially during the metamorphic climax, the most demanding developmental phase. Variations in the redox balance at different developmental stages may lead to a divergent response to pollution. Therefore, we recommend that studies using anuran larvae as biomonitors consider possible physiological differences during ontogeny in their respective analyses.